2009
DOI: 10.1200/jco.2009.27.15_suppl.e16145
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sorafenib and sunitinib on bone turnover markers in patients with bone metastases from renal cell carcinoma

Abstract: e16145 Background: Bone metastases (BM) from renal cell carcinoma (RCC) are common and associated with poor outcomes. While the multi-tyrosine kinase inhibitors (TKI's) sunitinib and sorafenib have advanced the treatment of metastatic RCC, their efficacy on BM is unknown. Urinary N-telopeptide (uNTX) is a marker of bone turnover measured in nmol/mmol creatinine. Elevated uNTX levels correlate with an increased risk of skeletal related events and mortality in patients receiving bisphosphonates for BM from a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Regarding the direct effect of TKIs on bone, Murray et al elegantly reported that sunitinib, a similar TKI to sorafenib, inhibited the osteoclast development and function mediated by macrophage colony-stimulating factor (M-CSF), a differentiating factor for osteoclasts ( 35 ). Furthermore, sorafenib decreased the urinary levels of N-terminal cross-linking telopeptide of type I collagen (NTx), a bone resorption marker, in renal cell carcinoma with bone metastasis ( 36 ). In the present case, the combination of sorafenib and denosumab displayed strong inhibitory effects against osteoclast-induced bone resorption, subsequently enabling calcium management for recurrent PC.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the direct effect of TKIs on bone, Murray et al elegantly reported that sunitinib, a similar TKI to sorafenib, inhibited the osteoclast development and function mediated by macrophage colony-stimulating factor (M-CSF), a differentiating factor for osteoclasts ( 35 ). Furthermore, sorafenib decreased the urinary levels of N-terminal cross-linking telopeptide of type I collagen (NTx), a bone resorption marker, in renal cell carcinoma with bone metastasis ( 36 ). In the present case, the combination of sorafenib and denosumab displayed strong inhibitory effects against osteoclast-induced bone resorption, subsequently enabling calcium management for recurrent PC.…”
Section: Discussionmentioning
confidence: 99%
“…The major contributor to poor quality of life and mortality in patients is from hypercalcemia. Different mechanisms of TKI's inhibitory effects on bone resorption have been proposed to be direct effects on osteoblasts and osteoclasts (Dewar et al 2005, Sahi et al 2009, Vandyke et al 2010, Aleman et al 2014; indirect actions via different pathways include osteoblast-derived RANKL, VEGF inhibition, PDGFR inhibition, macrophage colony-stimulating factor, SRC kinase, decrease in vitamin D-mediated intestinal calcium absorption, and altered calcium and phosphorus metabolism (Dewar et al 2005, Sahi et al 2009, Vandyke et al 2010, Aleman et al 2014. Sorafenib is such a multitarget TKI with anti-angiogenesis effect achieved by inactivating VEGFR-2, VEGFR-3, PDGFR-β, FGF receptor 1, c-Kit, Flt-3, and RET (http://hcp.nexavar-us.com/ mechanism-of-action/).…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…A prospective pilot study specifically designed to assess the effect of the anti-VEGFR multi-TKIs has recently been presented [Sahi et al 2009]. In patients with bone metastases from RCC and at least moderately elevated uNTX levels prior to treatment with sunitinib or sorafenib, there was significant trend to decrease uNTX levels during 12 weeks of therapy, but the fall was not as quick nor as marked as typically seen with bone-specific therapies such as bisphosphonates [Sahi et al 2009].…”
Section: Assessing the Response Of Bone Metastases To Therapymentioning
confidence: 99%